MULLIGANS MOBILISATION WITH MOVEMENT ( MWM ) RELIEVES PAIN AND IMPROVES FUNCTIONAL STATUS IN OSTEOARTHRITIS KNEE (International Journal of Physiotherapy, 2017)
Background: There are several manual therapy techniques for limited and painful knee flexion, but there are very few evidence about the effectiveness of Mulligan’s Mobilisation With Movement (MWM) in osteoarthritis of the knee. The objective of the study was to find the effect of MWM on pain and functional status in patients with osteoarthritis knee.Methods: 30 patients diagnosed with medial compartment tibiofemoral osteoarthritis of the knee were randomized into two groups ( experimental and control groups ) with 15 subjects in each group.The experimental group received medial glide MWM and medial rotation glide MWM in weight bearing and non-weight bearing positions after which the patients were asked to walk for a while. Conventional therapy in the form of shortwave diathermy (SWD), quadriceps strengthening and stretching of the calf and hamstrings was given to both the experimental and the control group. The intervention regimen lasted for seven days. Outcome measures were WOMAC score, VAS score and distance walked in 6-minute walk test.Result: The study showed significant improvement in VAS (p